Economic Burden of HIV Antiretroviral Therapy Adverse Events in the United States. (January 2016) - Dekoven, Mitch; Makin, Charles; Slaff, Samantha; Marcus, Michael; Maiese, Eric M.
Objective: To estimate health care costs associated with medical events identified as antiretroviral therapy (ART)-attributable adverse events (AEs). Methods: During September 2006 to June 2012, adults with ≥1 HIV International Classification of Diseases, Ninth Revision, Clinical Modification diagnosis code (042/V08), ≥1 claim for ART prescription (March 2007-June 2011; index date), and continuous health plan enrollment for ≥6 months pre- and ≥12 months postindex were included (IMS' PharMetrics Plus Health Plan Claims Database). Patients with events of interest/ART claim during preindex period or with pregnancy/hepatitis C virus diagnosis/hepatitis B virus/cancer/tuberculosis during the study period were excluded. Postindex medical events were defined as first diagnosis code of event with ART claim ≤60 days prior to start of the event. Results: Differences in median total all-cause health care costs observed for diabetes/insulin resistance management (US14 547 median all-cause health care costs during time periods identified as diabetes/insulin resistance medical events versus US11 237 without diabetes/insulin resistance events; P = .0021), lipid disorders (US12 825 versus US10 033; P = .0004), and renal disorders (US1389 versus US0; P < .0001). Discussion/Conclusion: Health care costs of ART AEs should be key consideration for payers/providers in HIV management.